Assessment of Career Skills at the High School Level - Khan, Sar B.; Khan, Sabir A. (Canadian Journal of Counselling and Psychotherapy, 2011)
An instrument containing 50 items, ten items in each of the five skill-areas of self-evaluation and development, career-awareness, career decision-making, employment-seeking, and work-effectiveness was administered to 939 grade 12 students from two large school boards. The results indicated that performance in both school boards was similar: females obtained significantly higher mean scores than males on three of the five subtests; and the Advanced Level students obtained significantly higher mean scores on all five subtests than the General Level students.